Determinants of retroplacental hematoma at the Maradi mother and child health center, Niger: a case‒control study - Zaratou Ali; Balkissa Issoufou Harouna; Habibatou Idé Amadou; Adamou Sayo Djibo (BMC Pregnancy and Childbirth)
Abstract Introduction Retroplacental hematoma is a paroxysmal accident that threatens maternal and fetal prognosis. It is a major emergency in obstetric pathology. The objective of this study was to identify the factors associated with retroplacental hematomas at the Maradi Mother and Child Health Center in 2022. Methods This was a case‒control cross-sectional analytical study that used patient records for the year 2022 from September 20 to October 20, 2023. The presence of a retropl placental hematoma was the outcome variable and was measured by a case (yes) or control (no) response. The exposure variables included sociodemographic characteristics, obstetric characteristics, care, progression of patients and neonatal characteristics. Pearson’s chi-square tests at the 5% significance level were used to analyze differences between categorical variables. All variables that had a bilateral p value < 0.05 in the bivariate analysis were introduced into the binary logistic regression model to identify factors associated with retroplacental hematoma. Results A total of 246 cases of retroplacental hematoma were recorded out of 4731 deliveries recorded during the study period, for an estimated frequency of 5.20%. The mean age of the patients was 29.41 ± 6.94 years. Factors associated with retroplacental hematoma included multiple parity [adjusted odds ratio (ORA): 0.38, 95% confidence interval (CI) (0.24–0.61)], fewer than 4 antenatal visits [AOR: 10.70, 95% CI (1.14–99.74)], blood transfusion [AOR: 2.01, 95% CI (1.11–3.60)], a newborn birth weight less than 2500 g [AOR: 1.92, 95% CI (1.53–2.42)] and fetal mortality in utero [AOR: 13.20, 95% CI (1.86–93.70)]. Conclusion This study identified the factors associated with retroplacental hematoma. Prevention requires regular, high-quality prenatal care. Early diagnosis and cesarean section improve maternal–fetal prognosis. Clinical trial number Not applicable.